Implementation Of Additive Ratio Assessment (Aras) Method For Online Reward Driver Provision - M. Iqbal Syahputra; Liza Yulianti; Devi sartika (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
Giving rewards to online drivers is one of the annual agendas carried out at Grab Bengkulu Branch to encourage driver motivation and professionalism in improving the quality of work. The obstacles faced in giving these rewards are due to the diversity of educational backgrounds, experiences, competencies and portfolios of the drivers, so we need a system that can assist in the process of giving rewards to drivers so that they do not become sluggish and experience difficulties. In the process of designing the application of this reward decision support system using the ARAS approach. The ARAS method is a method based on the intuitive principle that alternatives must have the largest ratio to produce an optimal solution. The ARAS method performs ranking by comparing the value of each criterion on each alternative by looking at the weights of each to obtain the ideal alternative. The implementation of the system uses the Visual Basic 2010 programming language. From the results of the tests carried out, it can be concluded that the best employee with a value of 0.90, the lowest value of 0.81